Upaya Menjaga Aset Sumber Daya Manusia Dalam Rangka Meminimalisasi Terjadinya Turnover Karyawan - Muhammad Sapruwan (JURNAL CITRA WIDYA EDUKASI, 2018)
Reason to stop working (resign) even though the company was already providing the best to its employees. This is experienced by PT "X" one of the oil palm plantation companies which have problems in keeping staff turnover. Therefore, it is necessary to do a research study to determine the factors that influence the occurrence causing employee turnover in PT "X". Percentage of turnover of employees at PT “X” that occurred in 2013 was 2.49%. Causes of employee turnover, among others: family, job satisfaction, retirement, career development, continuing ideals delayed, health, workload overload, got a better offer, location work. Turnover impact: cost losses during the process of recruitment and training, the activity delayed/lost so required over time. Make efforts to improve the system of clear working procedures, provide appropriate compensation for employee performance, system clear career path, develop competence and ability of employees.